Contrasting audio-taped feedback with minimal marking feedback in EFL writing - Hajimohammadi, Reza; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2011)
In this study, the researchers contrasted audio-taped feedback (ATF) with minimal marking (MM) among 82 EFL female pre-intermediate learners at Kish Air English Language Institute in Tehran-Iran. These 82 students were selected from among 126 pre-intermediate students according to their scores in a pre-intermediate version of Nelson English Language Test. The subjects were randomly divided into two groups of ATF and MM, each with 41 eligible subjects. In each group, they were assigned to write expository paragraphs of about 120 words during 8 sessions, one session for the pre-test, and another one for the post-test; the remaining sessions were allocated for the treatment. One of the groups received ATF and the other MM. A pre-test and a post-test were used before and after the treatment so as to contrast writing performances of the post- and pre-treatments. The results showed that the ATF subjects performed better than the MM in the post-test, while the MM subjects in post-test did not show any progress.